Analisis Hubungan Inflasi dan Pertumbuhan Ekonomi - Prima Lestari Situmorang; Riris Lawitta Maulina Siahaan (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This article is written because of the complex relationship between Inflation and economic growth and their often mutual influence on each other. At low and stable inflation rates, inflation can have a positive impact on economic growth. Moderate inflation often reflects strong demand in the economy, which encourages firms to increase production and investment. However, when hyperinflation occurs, it can damage the economy. this article is a literature review of various scientific articles on the relationship between inflation and growth. The data collection method is by document method and analyzed descriptively. From the articles reviewed, various findings were obtained stating that the relationship between inflation and economic growth is strongly influenced by the inflation rate, inflation expectations, and other macroeconomic conditions. Moderate and stable inflation tends to support economic growth, while high and uncontrolled inflation has significant negative effects. Prudent monetary policy is essential to keep inflation within limits that can support sustainable economic growth. To stabilize the economy, the role of the Central Bank is needed in controlling the money supply so that it does not decrease the value of money.